Viruses : A Very Short Introduction - Crawford, Dorothy H. (Oxford, New York Oxford University Press, 2011)
From modern pandemics such as HIV, swine flu and SARS, to stories of vaccination and antiviral drugs, this Very Short Introduction charts man's struggle against viruses. Outlining their origins, structure, and method of infection, Dorothy Crawford explores the vast variety of viruses, asking if we can live in harmony with them in the future
Include Illustration and Index
Keywords: Medical virology -- Viruses